Pengaruh Modal Kerja Dan Investasi Aktiva Tetap Terhadap Profitabilitas (Studi Kasus Pada PT Astra Internasional Tbk Periode 2015-2019) - Ega Prillia Santoso; Muhammad Agus Salim; M. Khoirul Abs (UNIVERSITAS ISLAM MALANG, 2020)
AbstractBasic of this research is to see the visual aspect of working capital and fixed asset investment on profitability measured using net profit margin (NPM) at PT Astra International Tbk for the period 2015 to 2019. This research uses explanatory research method, in this study using the method purposive sampling namely the determination of the sample with certain criteria as for the population in this study is all data from PT Astra International Tbk's financial statements from 2015 to 2019 so that the samples obtained in the form of financial position reports and income statements per quarter from 2015 to 2019. There are also analytical techniques used, namely multiple linear regression analysis, namely with research data in the form of secondary data. This research shows that working capital has no significant influence, whereas asset investment has a significant effect on profitability. Simultaneously working capital and fixed asset investment have a positive effect on profitability. Keywords: Working Capital, Fixed Asset Investment, NPM (Net Profit Margin) and Profitability